DOCK2 Is Critical for CD8+TCR− Graft Facilitating Cells to Enhance Engraftment of Hematopoietic Stem and Progenitor Cells. (15th September 2014) - Wen, Yujie; Elliott, Mary J.; Huang, Yiming; Miller, Thomas O.; Corbin, Deborah R.; Hussain, Lala-Rukh; Ratajczak, Mariusz Z.; Fukui, Yoshinori; Ildstad, Suzanne T.
Abstract: CD8 + TCR − graft facilitating cells (FCs) enhance engraftment of hematopoietic stem cells (HSCs) in allogeneic and syngeneic recipients. The mechanisms by which FCs promote HSC engraftment and tolerance induction have not been fully elucidated. Here, we provide data to support a critical role for dedicator of cytokinesis 2 (DOCK2) in multiple aspects of FCs function. DOCK2 −/− FCs exhibit compromised facilitative function in vivo as evidenced by the loss of engraftment-enhancing capability for c-Kit + Sca-1 + lineage − (KSL) cells, and compromised ability to promote KSL cell homing and lodgment in hematopoietic niche. Deletion of DOCK2 abrogates the ability of FCs to induce differentiation of naïve CD4 + CD25 − T cells into FoxP3 + regulatory T cells and interleukin-10-producing type 1 regulatory T cells in vitro. Moreover, DOCK2 −/− FCs are unable to promote survival of KSL cells when cocultured with KSL cells. DOCK2 −/− FCs also exhibit compromised migration to stroma-derived factor-1 in vitro and impaired homing to the bone marrow in vivo. In conclusion, our results demonstrate that DOCK2 is critical for FCs to maintain its immunomodulatory function and exert its trophic effects on KSL cells. These findings may have direct clinical relevance to promote HSC engraftment for treatment of autoimmunity, hemoglobinopathies, and to induce transplantation tolerance. Stem Cells 2014;32:2732–2743